MANFAAT DAUN KATUK (Sauropus androgynous L. MERR.) UNTUK MENINGKATKAN KUALITAS ASI PADA IBU MENYUSUI - admjurnalsiji polibara; Aditya Robby Zhuliyan; Lutfiah Safirah; Saryono (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2021)
The problem of breastfeeding is part of the discomfort problem for postpartum mothers for 2 hours after delivery. This problem often causes trauma to postpartum mothers during breastfeeding, psychological disorders, and increased morbidity in both mothers and babies due to insufficient breastfeeding. Katuk leaf extract is a medicinal plant that has a role to increase milk production. Katuk (Sauropus androgynus (. (L.) Merr) has been known to increase milk production since ancient times in Indonesia. The aim of this research was to see the potential of katuk leaves to improve the quality of breastfeeding mothers. This research was conducted using in-depth interviews with purposive sampling technique. The results showed that there were variations in the use of katuk in 4 communities in East Java, the highest utilization of katuk was found in osing. Katuk leaves are one type of galactagogue herb which is believed to increase levels of prolactin and oxytocin, and contains nutrients that can be used as raw material for breast milk synthesis. The increase in milk volume is caused by katuk leaves which contain phytochemical compounds, namely alkaloids (papaverine) and sterols (phytosterols) which can increase levels of prolactin and oxytocin, and contain nutrients that can be used as raw material for breast milk synthesis. 100 g of fresh katuk leaves contain 79.8 g water, 7.6 g protein, 1.8 g fat, 6.9 g carbohydrates, and an energy value of 310 kJ. The conclusion of this study is, katuk leaves are proven to improve the quality of breast milk in nursing mothers. Key words: katuk leaves, Sauropus androgynus L. Merr., Breast milk, and breastfeeding mothers.